Determinan Indeks Pembangunan Manusia di Kabupaten Aceh Selatan - Tri Aprian Yudhistira; Puti Andiny; Yani Rizal; Safuridar Safuridar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The Human Development Index is an indicator of the progress of a region. Achieving development cannot be separated from the quality of people in a region. To see the extent of success in human development, the United Development Program (UNDP) has issued an indicator, namely the Human Development Index (HDI). HDI is a benchmark for achieving higher quality human development. There are three basic dimensions as a reference for measuring the Human Development Index, namely including a long and healthy life, knowledge, and a decent standard of living. This research aims to see the influence of Poverty, Gini Index, and Economic Growth on the Human Development Index in South Aceh Regency 2009 - 2023. The data used in this research is secondary data in the form of a time series taken from the last 15 years sourced from the Agency. South Aceh Regency Statistics Center (BPS) using a quantitative approach. The method used is multiple linear regression analysis. Based on the research results, it can be concluded that poverty has a positive and significant influence on HDI. The Gini Index has a negative and insignificant influence on HDI. Economic Growth has a positive and insignificant influence on HDI in South Aceh Regency 2009-2023.